The Strategy for Implementing Pai Curriculum Based on Local Wisdom Between Baitul Kirom Islamic Boarding School and Al-Kirom Vocational School - Arifin, Jaenal; Yusuf, Muhammad; Subandi, Subandi; Muslimin, Ahmad (International Journal on Advanced Science, Education, and Religion, 2025)
This research examines the strategy for implementing the Islamic Religious Education (PAI) curriculum based on local wisdom which was developed through collaboration between Baitul Kirom Islamic Boarding School and Al-Kirom Subing Karya Vocational School. The aim of this research is to analyze the process of planning, implementing and evaluating the Islamic boarding school curriculum which is integrated into the vocational education context. Using a qualitative approach and case study method, data was collected through participant observation, in-depth interviews and documentation. The research results show that curriculum planning is carried out through systematic stages which include goal formulation, curricular content preparation, learning strategies, and evaluation design. At the implementation stage, the role of teaching staff competence is the key to success, supported by the use of classical books such as Ta'lim al-Muta'allim and Fathul Qarib, as well as the application of the bandongan method. Evaluation of implementation is carried out taking into account contemporary needs of students and societal expectations. The evaluation results show that the integration of the Islamic boarding school curriculum significantly increases the internalization of Islamic values, forms religious character, and improves the quality of students' religious understanding. This integrative model has succeeded in creating an educational ecosystem that is not only responsive to the demands of the world of work, but also maintains spiritual values. This research recommends strengthening teacher capacity, diversifying technology-based learning resources, and increasing inter-institutional networks as sustainable strategies.